Multiple Endoscopic Biopsy Sites increase detection of Helicobacter Pylori infection: a multi-centre study - Ahmad Hamidi, Ahmad Junaidi; Mahno, Noor Ezmas; Din, Jiffre; H, Azmi H; A.R, Azlinda; Sarif, Mat Salleh; Othman, Ahmad Faidzal; S. T., Azmi; Kasian, Junaini; Amjad, Nasser Muhammad (Surgical Society of Northern Greece, 2021)
Background: Helicobacter pylori infection affects almost half of the population and remains clinically significant in chronic gastritis and gastric malignancy. However, its prevalence is found to be low in Pahang, Malaysia population where the practice of single antral biopsy during endoscopy has been advocated. Our aim for this research is to determine the role of multiple gastric biopsy sites during endoscopy (OGDS) to increase the detection of Helicobacter pylori infection. The recommended 5 biopsy sites in the Updated Sydney System in which includes antrum, incisura angularis and body of stomach. Methodology: This is a cross sectional study of 141 patients with clinical diagnosis of gastritis or dyspepsia who underwent OGDS in 2 tertiary hospital in Pahang, Malaysia from January 2016 to December 2016. Five biopsy sites have been obtained and tested with CLO test and send for histology. The positive result for Helicobacter pylori infection by CLO test and/ or histology together with sociodemographic data, endoscopic diagnosis and histology characteristics were recorded and analyzed using IBM SPSS Statistic version 23. Results: Total of 17 patients were diagnosed with Helicobacter pylori infection, making the prevalence of the infection to 12%. No significant difference seen in most of the parameters identified. However, we found out that single antral biopsy can missed the infection rate up to 35%. Conclusion: Multiple biopsy sites during endoscopy can increase detection of Helicobacter pylori infection.